Characterization of an edible coating based on alginate and essential oils (Research, Society and Development, 2022)
The use of films, coatings or edible films applied to products is of growing importance in the food industry. Alginate is a widely used polysaccharide and rosemary and oregano oils have been applied as antimicrobial and antioxidant agents. The resistance of these films and the mass transfer through them are important parameters and must be studied. Thus, this work aimed to characterize an edible covering based on alginate and essential oils (rosemary and oregano). It can be seen that the addition of oils did not influence (p